IMPROVING COLLEGE STUDENTS’ SPEAKING SKILL THROUGH VIDEO PROJECT - Mufidah Yusroh (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2019)
Technology is very much part of today’s life. It has been used as a tool in language learning throughout the world at all different levels especially adult learners. Nowadays, it is important to engage students to speak confidently and learn independently in their daily activity as students. However, the level of their speaking skills is still not satisfactory. They still have difficulty to communicate using English. The purpose of this study is to examine whether video project able to improve the speaking skill of the students. A Classroom Action Research design was applied. The data were collected through small group and individual activities. Video project competition was done for the final project. This study was conducted in two cycles of seven meetings in each cycle. Based on the analyses, data showed that there are changes from cycle 1 to cycle 2. In cycle 1, the percentage of students English skill is 54% and it is increased become 75% in cycle 2. The average result of percentage in cycle 1 to cycle 2 is 21%. The result of the data showed that the use of video project could be one of the best alternatives to improve the students’ speaking skill.